Justice Beyond Borders: Strengthening International Alliances to Eradicate Human Trafficking in Southeast Asia - Nur Aisyah Abdurrahman; Suwinda Suwinda; Lisa Ikhsana; Muhammad Habiby Abil Fida Safarin; Rifki Fakihudin; Sulaiman Tan; Wipaporn Sawasdee (Universitas Negeri Semarang, 2025)
Human trafficking remains a critical issue in Southeast Asia, exacerbated by socio-political, economic, and cultural factors. This paper examines the concept of justice, advocating for enhanced international cooperation to effectively combat human trafficking in the region. It identifies the limitations of current national-level approaches, which fail to address the transnational nature of trafficking networks. The paper highlights significant normative and legal gaps, such as inconsistent definitions of trafficking, lack of harmonized laws, and weak enforcement mechanisms, which undermine anti-trafficking efforts. Drawing on international law and human rights frameworks, the paper argues for a more coordinated approach among Southeast Asian nations, international organizations, and civil society. Central to this approach is legal harmonization, improved intelligence sharing, and stronger enforcement to combat trafficking. The paper also integrates restorative justice and victim-centered policies, emphasizing comprehensive rehabilitation for survivors. By analyzing successful case studies and pinpointing gaps in existing legal frameworks, it offers practical recommendations for policymakers, including the establishment of regional task forces and the creation of victim support networks. Ultimately, this paper advocates for a paradigm shift in the fight against human trafficking, calling for a holistic, justice-oriented approach that goes beyond borders and empowers victims and frontline actors in Southeast Asia.